Policy Windows: Sociopreneurship Activity Through Development of Turtle Breeding Ecotourism in Mapak Indah Beach - Mey Susanti AS; Johan Mashuri (Jurnal Ilmiah Ilmu Administrasi Publik, 2020)
Indonesia is one of the few countries in the world which becomes a natural habitat for turtles.However, like other countries, the Indonesia’s turtle population are prone to extinction. All species of see turtles in Indonesia’s waters are protected under the Government Regulation Number 7, 1999 concerning preservation of plant and animal species. Despite having the legal status, the turtle preservation is not fully comprehended and even ignored by the number of people. The development of turtle-based ecotourism is an alternative source of income. Mapak Indah Beach is considered to be a representative area for this ecotourism activity. However, finding from tourism and ecological activities shows no satisfactory results in combining the two activities. Sociopreneurship activities in the management of the Mapak Indah Beach turtle breeding ecosystem require an in-depth study to be able to access the policy windows of the Mataram City Government (the public agenda becomes the government's agenda). Strategic policies are: (1) an increase of coordination and roles among stakeholders; 2) a capacity building for management and procurement of sarpras; and (3) an increase of knowledge and skills of the local communities.